CHARACTERISTICS NESTING BEACH OF GREEN TURTLE (Chelonia mydas) IN CHAGAR HUTANG REDANG ISLAND TERENGGANU MALAYSIA - Muhammad Rizky Rinaldi; Efriyeldi Efriyeldi; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Green turtle (Chelonia mydas) is one type of reptile that is protected because endangered. This research was conducted in March-April 2018 in the Chagar Hutang of Redang Island, Terengganu, Malaysia. The purpose of this study is to determine the characteristics of the nesting beach of green turtle(C. mydas). The method used in this study is the survey method. There are 3 observation stations, station 1 located in a location that has little vegetation and there is a tide pool around the station. Station 2 is located in a dense vegetation and has a gentle slope category. While station 3 is located in an area near the less and the has less dense vegetation. The slope of the beach at each station were measured. Characteristics of nesting beaches include the slope, width,flora and fauna, the type of substrate, air temperature and sea water temperature. The  results of the study showed that the slope of these coast ranged from 3.65 to 5.35˚ classified as sloping. The width of the beaches were quite wide, ranged 26.47-36.46 meters. The common vegetation consist includes ketapang (Terminalia cattapa), sea pandanus (Pandanus tectorius) and babakoan (Scaevola raccada). While the common fauna includes ghost crab (Ocypodinae), monitor lizards (Varanus), fire ants (Solenopsis), hermit crabs (Paguroidea), and various types of corals (Coral). The type of substrate was gravel sand with air temperature in the range of 27-29ºC, while the sea water temperature was in the range of 28-29ºC. Keyword: Cheloniamydas, Characteristics Nesting Beach, Chagar Hutang